"I Want the Piece of Paper that Is My History, and Why the Hell Can't I Have It?": Original Birth Certificates and Adoptive Identity. Issue 3 (3rd July 2022) - Rizzo Weller, Melissa
ABSTRACT: This study focused on how adopted adults who have reunited with at least one birth family member experienced identity shifts related to their original birth certificates (OBCs). Framed by the Communication Theory of Identity (CTI), 50 adopted adults discussed their experiences related to their OBCs and how their identities are connected to this symbol through three of the layers of CTI, the personal, enacted, and relational layers. Participants discussed the presence of an ambiguous and unsolvable identity that interpenetrated with their other identity layers. Findings extend CTI to include an additional layer for adoptees – phantom identity – which can explain the life adoptees would have lived had they not been adopted. This identity was salient for participants as it manifested in ways such as expressing frustration with obstacles in gaining access to their OBC and refocusing their professional life to support other adopted adults. Moreover, findings offer implications for the examination into current adoption record practices in the United States, additional state mutual consent registries, and increased access to adoption-competent counselors for adoptees.